Detection of non-formal and informal learning in Learning Communities supported by social networks in the context of a cooperative MOOC - Cruz-Benito, Juan; Borras-Gene, Oriol; Garcia-Penalvo, Francisco J.; Fidalgo Blanco, Angel; Theron, Roberto (2015 International Symposium on Computers in Education (SIIE), 2015)
This paper retrieves information and makes basic analysis about the participation of users involved in Cooperative MOOCs in Learning Communities supported by hypermedia environments like the social networks. In order to perform this study, the interaction of a set of users enrolled in a course within the iMOOC platform has been analyzed, in which MOOC courses are implemented based on concepts like connectivism, collaborative learning, gamification or adaptivity. Specifically, this study deals with obtaining information about the discussions that take place in learning communities created using social networks like Google+ and Twitter in parallel of the activities performed inside the iMOOC platform. Through this information, this paper tries to distinguish the types of learning that occurs in those discussions (non-formal and informal learning), estimating also how users interact with tagged content in social networks, and how that allows students -users- to continue or create conversations that help to expand or strengthen the content they treated during the MOOC course.